The Effect of Education on Mothers' Knowledge of Infant and Child Feeding for Stunted Children as A Preventive Measure Against Tuberculosis in Children - Arisjulyanto, Dedy; Siregar, Neny San Agustina; Kusuma, Ardhanari Hendra (Indonesian Journal of Global Health Research, 2024)
Children who experience stunting are at a higher risk of being infected with infectious diseases, including tuberculosis (TB). By increasing mothers' knowledge about proper feeding practices, it is expected that the prevalence of TB among stunted children can be reduced. This study aims to examine the effect of education on mothers' knowledge regarding infant and child feeding practices for stunted children as a preventive measure against tuberculosis (TB) in children. The study utilized a one-group pretest-posttest design and was conducted in the Kosiwo Community Health Center's service area. A total of 45 participants were selected using a total sampling method. Data in this study were collected before and after the intervention using a validated and reliable questionnaire on children's nutrition knowledge and a questionnaire on children's knowledge of tuberculosis (TB), with Cronbach's alpha values of 0.897 for the nutrition knowledge questionnaire and 0.946 for the children's knowledge of TB questionnaire. The results were analyzed with the Paired T-Test, which showed that the mean knowledge score regarding Infant and Child Feeding before the intervention was 12.89. After the educational intervention, this score increased by 11.11 points to 24.00, with a p-value of 0.000, indicating statistical significance as it is less than α = 0.05. Additionally, the mean knowledge score concerning TB transmission in children was 14.89 before the intervention, rising by 9.78 points to 24.67 afterward, also yielding a p-value of 0.000, which is below α = 0.05.